Intestinal microflora, body fat profiles and performance of male Tegal duck fed diet supplemented with red tomato extract - Rochman, F.; Ismadi, V. D. Y. B.; Krismiyanto, L.; Suthama, N. (Journal of the Indonesian Tropical Animal Agriculture, 2024)
The study was conducted to evaluate the effect of dietary supplementation of red tomato extract (RTE) on intestinal microflora, fat digestibility, body fat (meat fat mass, abdominal fat), and performances of male tegal duck. One hundred birds of male tegal ducks of 3 weeks old (initial body weight was 507.74±31.86 g) were randomly divided into 4 treatments with 5 replications (5 birds each) in a completely randomized design. Dietary treatments were basal diet without RTE as a control (T0), basal diet added with 0.10% RTE (T1), basal diet added with 0.15% RTE (T2) and basal diet added with 0.20% RTE (T3). Parameters measured were lactic acid bacteria (LAB), coliform, intestinal pH, fat digestibility, meat fat mass, abdominal fat, blood concentrations of malondialdehyde (MDA) and superoxide dismutase (SOD), body weight gain (BWG), carcass weight, feed consumption, and feed conversion ratio (FCR). Data were subjected to analysis of variance and continued to Duncan multiple range test when the treatment indicated significant (p<0.05) effect. Supplementation of RTE at higher level significanly (p<0.05) increased lactic acid bacteria (LAB), concentration of superoxide dismutase (SOD), carcass weight and body weight gain (BWG), while fat digestibility, meat fat mass, abdominal fat, malondialdehyde (MDA), intestinal pH, coliform counts and feed conversion ratio decreased (p<0.05), as compared to control. Feed consumption tended to decrease but not significant (p>0.05). In conclusion, feeding red tomato extract at a level of 0.20% (T3) can be categorized as effective in improving intestinal bacterial balance, body fat, increasing superoxide dismutase (SOD), an antioxidant enzyme, and performances of male tegal duck.